ANEMIA GIZI BESI PADA REMAJA PUTRI DI WILAYAH KABUPATEN BANYUMAS - sari, Hesti Permata; Dardjito, Endo; Anandari, Dian (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2016)
Iron deficiency anemia in adolescents still be a problem. If it untreated, it will continue into adulthood and contribute greatly to maternal mortality, premature birth, and low birth weight babies. The aim of this studi was to determine the risk factors on the incidence of adolescent girls iron deficiency anemia in urban and rural areas Banyumas. This study conducted with cross sectional approach to 120 sample of adolescent girls who study at the high school. Data knowledge of nutrition and body image obtained through questionnaires, consumption obtained through food recall, Hemoglobin levels with test strips, and analysis by chi square test and multiple logistic regression. The samples of the study, 70 came from urban and 50 were from rural, 92.9% of urban adolescent  girls and 76% of adolescent  girls in rural sample anemic. Bivariate analysis showed that factors associated with the incidence of iron deficiency anemia in adolescent girls in urban were protein intake and iron intake. Multivariate showed that the most factor on the incidence of iron deficiency anemia in urban was protein intake. We expected Dinas Kesehatan to have a collaboration with the Dinas Pendidikan to solve the problem of adolescent anemia